COVID-19 and pediatric out-of-hospital cardiac arrest using U.S. registry database - Christopher Schmitt; Gary Beasley; Karine Guerrier; Jennifer Kramer; Maryam Y. Naim; Heather Griffis; Bryan McNally; Paul S. Chan; Rabab Al-Araji; Joseph Rossano (Resuscitation Plus)
Background: Out-of-hospital cardiac arrests (OHCA) increased in the adult population during the COVID pandemic.1,2,3,4,5,6,7,8 Objectives: We aimed to determine if OHCAs increased in the pediatric population during the COVID pandemic and whether the pandemic exacerbated pre-existing racial and socio-economic disparities.13,17,18,19,20 Methods: Utilizing data from 2015 to 2020 from the Cardiac Arrest Registry to Enhance Survival (CARES) database, 13,513 pediatric OHCAs were analyzed. Age categories included infants (0–<1 year), children (1–12 years) and adolescents (13–18 years). This included information on patient demographics, use of CPR (cardiopulmonary resuscitation) or AED (automatic external defibrillator), outcomes, COVID prevalence, and socioeconomic variables. Results: In the pediatric population, there was no increase in OHCAs during the COVID pandemic, however in the adolescent population there was an increase in OHCA incidence from 0.29 to 0.40 arrests per 1 million total residents (p < 0.0001), and a decrease in the infant population from 0.861 to 0.803 events per 1 million total residents (p = 0.02). The pandemic worsened the burden of OHCAs in communities with lower socioeconomic status and in which COVID was more prevalent. Disparities of CPR or AED use and survival outcomes were seen based on race, sex, and socioeconomic factors, however none of these disparities were further augmented by the COVID pandemic. Conclusions: Adolescent populations showed higher rates of OHCAs during the COVID pandemic, especially in areas with higher COVID incidence. Infants, however, had slightly decreased rates, which may be related to changes in other respiratory infections, and parental behavioral changes during the pandemic.